Smallholder pig farming in Uganda: A day in the life of a research for development project - International Livestock Research Institute (International Livestock Research Institute, 2014)
Using images and text this photofilm shows the work of two projects which seek to improve the management of smallholder pig farming systems in Uganda: the IFAD-supported Smallholder Pig Value Chains Development project and the BMZ-supported Safe Food, Fair Food project.